The effects of corporate bonds on employment: Early evidence from Greece - Sotirios Karagiannis; Dimitrios D. Thomakos (Review of Economic Analysis (REA), 2020)
This study investigates the impact of corporate bonds issued by Greek listed firms on employment. Even though external financing and the effects on employment has been studied in the literature, we extend the existing literature by focusing for the first time on the specific role of corporate bonds on employment. We have collected all the relevant papers on this line of the literature and concisely report them in a table format and then use them in analyzing our results. Our empirical analysis is based on a panel dataset from 2001 to 2014 and we examine the effect of corporate bonds in the pre and post period of the Greek economic crisis, in which the banking system is vulnerable and unable to provide financing to the firms. The results suggest that corporate bonds have a positive effect on employment in the pre-crisis sample, denoting that firms hire employees and proceed to investment choices. On the contrary, during the recession, corporate bonds have a negative effect on employment. Firms reduce their costs and try to control their debt obligations by issuing corporate bonds.
Keywords: G32; J23; M51; 330; Corporate Bonds; Corporate Debt; Employment; Greek Economic Crisis